2004
DOI: 10.1002/dvdy.20018
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor receptor‐3 is expressed in undifferentiated intestinal epithelial cells during murine crypt morphogenesis

Abstract: Prior studies have demonstrated that fibroblast growth factor receptor-3 (FGFR-3) regulates proliferation of undifferentiated intestinal epithelial cells in vitro. However, the function(s) of FGFR-3-mediated signaling during intestinal development and epithelial differentiation in vivo remain unknown. The goal of this study was to define the temporal, regional, and cell-specific patterns of FGFR-3 expression and its ligands during normal intestinal ontogeny and epithelial regeneration. Both the IIIb and IIIc i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 54 publications
(64 reference statements)
2
32
1
Order By: Relevance
“…Our previous findings that FGFR-3 and its cognate ligands FGF1, FGF2, and FGF9 are coordinately expressed at high levels during postnatal intestinal development suggested that this signaling pathway mediates the morphogenic events at this time (50). Although our prior study did not define the specific role(s) of FGFR-3 in regulating developmental events in the intestine, the observation that expression of FGFR-3 was restricted to undifferentiated epithelial cells within the lower portion of the crypt, a region known to house the epithelial stem cell population, further suggested that signaling through FGFR-3 is important in mediating some aspect of epithelial morphogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our previous findings that FGFR-3 and its cognate ligands FGF1, FGF2, and FGF9 are coordinately expressed at high levels during postnatal intestinal development suggested that this signaling pathway mediates the morphogenic events at this time (50). Although our prior study did not define the specific role(s) of FGFR-3 in regulating developmental events in the intestine, the observation that expression of FGFR-3 was restricted to undifferentiated epithelial cells within the lower portion of the crypt, a region known to house the epithelial stem cell population, further suggested that signaling through FGFR-3 is important in mediating some aspect of epithelial morphogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Our studies focused on the consequence of FGFR-3 deletion during stem cell proliferation and crypt morphogenesis, dynamic processes that take place during postnatal intestinal development. Arnaud-Dabernat and colleagues examined the consequences of FGFR-3 deletion on the replication of transit amplifying cells in the unperturbed adult intestine, a developmental stage at which expression of FGFR-3 in crypt epithelial cells is low, the number of crypts is static, and crypt stem cells are relatively quiescent compared with the suckling mouse intestine (50). It is possible that the response of the transit amplifying cell population of the adult intestine to FGFR-3 signaling is different from that of stem cells of the developing intestine.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations